The drag crisis phenomenon on an elite road cyclist - A preliminary numerical simulations analysis in the aero position at different speeds - Forte, P.; Morais, J. E.; Neiva, H. P.; Barbosa, T. M.; Marinho, D. A. (International Journal of Environmental Research and Public Health, 2020)
The drag crisis phenomenon is the drop of drag coefficient (Cd) with increasing Reynolds number (Re) or speed. The aim of this study was to assess the hypothetical drag crisis phenomenon in a sports setting, assessing it in a bicycle-cyclist system. A male elite-level cyclist was recruited for this research and his competition bicycle, helmet, suit, and shoes were used. A three-dimensional (3D) geometry was obtained with a 3D scan with the subject in a static aero position. A domain with 7 m of length, 2.5 m of width and 2.5 m of height was created around the cyclist. The domain was meshed with 42 million elements. Numerical simulations by computer fluid dynamics (CFD) fluent numerical code were conducted at speeds between 1 m/s and 22 m/s, with increments of 1 m/s. The drag coefficient ranged between 0.60 and 0.95 across different speeds and Re. The highest value was observed at 2 m/s (Cd = 0.95) and Re of 3.21 × 105, whereas the lower Cd was noted at 9 m/s (Cd = 0.60) and 9.63 × 105. A drag crisis was noted between 3 m/s and 9 m/s. Pressure Cd ranged from 0.35 to 0.52 and the lowest value was observed at 3 m/s and the highest at 2 m/s. The viscous drag coefficient ranged between 0.15 and 0.43 and presented a trend decreasing from 4 m/s to 22 m/s. Coaches, cyclists, researchers, and support staff must consider that Cd varies with speed and Re, and the bicycle-cyclist dimensions, shape, or form may affect drag and performance estimations. As a conclusion, this preliminary work noted a drag crisis between 3 m/s and 9 m/s in a cyclist in the aero position.